PERANCANGAN KEY PERFORMANCE INDICATORS KINERJA SUPPLY CHAIN PT.XYZ DENGAN PENDEKATAN BALANCED SCORECARD - Joko Hardono; Henri Ponda (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2018)
Supply Chain performance measurement PT.XYZ had only seen from the productivity of the Company. Productivity is only able to measure the performance of the internal process, while the internal process is but one link in the chain of Supply Chain. Companies need to design a model of supply chain performance measurement as a whole and integrated in a causal relationship, ranging from suppliers, internal processes to customers, in order to know the effectiveness of supply chain companies. Balanced scorecard meet the necessary perspective. Balanced scorecard model is used as a framework for designing of Key Performance Indicator (KPI) of supply chain performance PT.XYZ. KPI is design based on 4 perspectives, that is : internal processes, customers, learning and growth and perspective financial. Weighting to determine priorities between perspective and KPI performed using Analytical Hierarchy Process (AHP). Result from th eanalysis is generated 20 KPI. Internal process perspective contain 9 KPIs with total weight 21,0 %, Customer perspective contain 6 KPIs with total weight 42,6 %, Learning and growth perspective contain 4 KPIs with total weight 17,5 %, Shareholder perspective contain 1 KPI with total weight 19,0.